2007
DOI: 10.1667/rr0649
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Radiation Response of Primary Keratinocytes and Fibroblasts from Patients with Cervix Cancer

Abstract: The aim of the present study was to examine, using the micronucleus (MN) assay, the low-dose radiation response of normal skin cells from cancer patients and to determine whether the hyper-radiosensitivity (HRS)-like phenomenon occurs in cells of these patients. Primary skin fibroblasts and keratinocytes derived from 40 patients with cervix cancer were studied. After in vitro gamma irradiation with single doses ranging from 0.05 to 4 Gy, MN induction was assessed. For each patient, the linear-quadratic (LQ) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…To provide evidence to support the claim that RBE is dependent on radiosensitivity, ideally, proton RBE would be determined for two types of skin cells: fibroblasts and keratinocytes (at least twice as resistant as fibroblasts) (Słonina et al 2007). Keratinocytes are target cells involved in acute epidermal reactions to radiotherapy, whereas fibroblasts are target cells responsible for late effects (fibrosis) in skin and other organs (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide evidence to support the claim that RBE is dependent on radiosensitivity, ideally, proton RBE would be determined for two types of skin cells: fibroblasts and keratinocytes (at least twice as resistant as fibroblasts) (Słonina et al 2007). Keratinocytes are target cells involved in acute epidermal reactions to radiotherapy, whereas fibroblasts are target cells responsible for late effects (fibrosis) in skin and other organs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was approved by the Ethical Committee of the Regional Medical Chamber in Kraków. The procedure for obtaining and preparation of the cells was described previously (Słonina et al 2007, 2008). We used fourth- to sixth-passage fibroblasts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the low effective activation of ATM and the linked ATM-dependent ''early'' G2 checkpoint, it was predicted that G2-phase cells that survive the exposure to doses less than $0.3 Gy will experience an overall reduced fidelity of repair compared with cells in the other phases of the cell cycle, and therefore, these G2-phase cells will be prone to heritable genetic changes (8). Recently, researchers from Poland reported low-dose HRS/IRR in primary keratinocytes and fibroblasts from patients with cervix cancer for micronucleus induction by X-rays (26). Russian researchers found that the HRS/IRR could be observed by the anaphase method and micronucleus assay in X-ray using Chinese hamster V79 cells and human melanoma cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative data are currently in favor of an individual response to medical exposures . Slonina et al firstly revealed that a low-dose hyper-susceptibility could be an individual characteristic (Slonina et al, 2006(Slonina et al, , 2007. These authors highlighted more X-ray radiation-induced DNA damages in human cells (fibroblasts and keratinocytes) from some patients at low-dose.…”
Section: Radiobiological Study Using Non-tumoral Breast Epithelial Cellsmentioning
confidence: 99%